A proximal type epithelioid sarcoma of the vulva with multiple distant metastases: A case report and review of the literature - Hyewon Chung; Tae-Kyu Jang; Sun Young Kwon; Jinkyeong Ha; So-Jin Shin (Elsevier, 2021)
Epithelioid sarcomas (ESs) of the vulva are extremely rare soft tissue tumors characterized by an aggressive clinical course and a poor prognosis. The proximal type of ES occurs in the trunk and external genital area and has higher recurrence and distant metastasis rates than the distal type, which is found in the upper and lower extremities. We describe a case of a vulvar ES in a 24-year-old patient who was referred from the department of plastic surgery with protruding mushroom-like lesions in multiple areas, including the lower abdomen, whole vulva, anus, and both inguinal lesions. A biopsy of the lesions confirmed a proximal-type ES. Computed tomography and magnetic resonance imaging revealed multiple metastatic lesions in several regions, including the perineum, vagina, and inguinal regions; nodal metastases in the left external iliac and right inguinal region; and distant metastases in the lungs, pleura of the left lung, bones, and soft tissue. The patient underwent active palliative radiotherapy, followed by chemotherapy, and showed a partial response to treatment. Nineteen months after the initial diagnosis, the patient expired due to cancer progression and pneumothorax.